Corporate Accountability and Human Rights: A Legal Analysis of the UN Guiding Principles - Santosa, Tomi Apra; Hamdani, Hamdani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the role of the United Nations Guiding Principles on Business and Human Rights (UNGPs) in strengthening corporate accountability for the protection and promotion of human rights. The UNGPs as a global normative framework affirms the state's obligation to protect, corporate responsibility to respect, and access to recovery for victims of human rights violations. Through a normative juridical approach, this study examines the relevance of these principles in international legal practice and their implementation in national law, and identifies the extent to which these instruments are able to encourage corporations to act ethically, transparently, and accountably. The results of the analysis show that although UNGPs have significant normative power, their soft law characteristics pose challenges in consistent application across jurisdictions. Nevertheless, the UNGPs have contributed to the establishment of global standards that encourage companies to integrate human rights principles in business governance, as well as providing an important reference for policymakers and judicial institutions in handling cases of abuse. This study emphasizes that to strengthen the effectiveness of UNGPs, it is necessary to harmonize regulations, more stringent law enforcement mechanisms, and increase corporate awareness of their social responsibilities in the international and national legal systems